Employment of friendly aliens (Hansard extract) - Waverley, John Anderson, Viscount Westdean, 1883?-1958
C01-0005-001 EMPLOYMENT OF FRIENDLY ALIENS. Replying to Mr. W. ROBERTS (Cumberland, N., Opp. L.), Sir J. ANDERSON, Home Secretary (Scottish Universities, Nat.), said that: it was proposed to utilise the services of friendly aliens in any direction in which they could advantageously be employed without prejudicing the interests of British subjects. To give effect to this policy, he proposed very shortly to make a general order which would have the effect that, where an alien's stay in this country was made subject to a condition prohibiting him from taking employment, he would be free until further notice to enter any employment approved by the Ministry of Labour. HOUSE of COMMONS, 19th October, 1939. 292C/946/1/5